Skema Kepemimpinan Kepala Sekolah dalam Mewujudkan Mutu Pendidikan Di SMP Islam Al-Faat Bara Dompu NTB - Muhasir; Evan Hardianto; Nona Yuliana (AL-FURQAN, 2023)
This research is motivated by the establishment of the Islamic Middle School Al-Faat Bara Dompu NTB in 2021, with the leadership of the first principal. The purpose of this research is to find out how the leadership scheme of the principal of the West Halmahera Insan Cendekia School in realizing school quality. This research is a descriptive qualitative research, with a phenomenological approach that occurs in the field. Collecting data using observation, in-depth interviews and documentation. The data analysis technique used three analysis lines, namely data reduction, data presentation and verification. The results of this study indicate that: The scheme of implementing and evaluating the quality of education at the Al-Faat bara-Dompu Islamic Middle School is carried out in three ways: the first: providing adequate facilities and infrastructure, second: increasing teacher competence and third: developing the potential of students in the field of science and technology and IMTAQ as the school's flagship program. Full support from the central government and local governments for school development is a supporting factor in realizing quality. The results obtained from improving the quality of education are, students of school construction facilities, and achievements obtained from competitions in the field of Science and technology as well as, Al-Faat Sudat Islamic Junior High School recognized and registered with the Ministry of Education and Culture of the Republic of Indonesia.